Analysis of the correlation of excessive use of folic acid in pregnancy with Autistic Spectrum Disorder (ASD) (Research, Society and Development, 2024)
Autism Spectrum Disorder (ASD) is characterized by a neurodevelopmental disorder with atypical behavioral manifestations, deficits in communication and social interactions, and repetitive and stereotyped behavior patterns. Folic acid is one of those responsible for the neurodevelopment of the fetus during pregnancy, the lack of it can cause complications or disabilities in the newborn. Therefore, this study aims to gather articles on the use of folic acid during the gestational period and evaluate its correlation with births of children with Autism Spectrum Disorder. The search strategy was the selection of articles in Portuguese and English in the PubMed, SciELO and ScienceDirect databases, during the period from February to June of 2024. Based on the findings of the selected articles, correct folate intake can reduce the chance of the embryo developing neural tube defects by up to 70%, which can occur in 1 in every 1,000 pregnancies. When analyzing the risk-benefit of supplementation with folic acid in the correct dose, it is concluded that the benefits of folic acid supplementation outweigh the possible harm.